2012
DOI: 10.1016/j.jpainsymman.2011.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cancer Patient Well-Being With a Nonpharmacological, Heritage-Focused Intervention

Abstract: Findings indicate a future role for heritage-focused practices in enhancing health care environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…Thomson et al, 2012b). The act of taking an object into one's hands can be a 20 powerful experience (Samuels, 2008) particularly in the context of a hospital environment where opportunities for tactile stimulation are often minimal for long periods of time (Ander et al 2013).…”
Section: Wellbeing and Engagement Processesmentioning
confidence: 99%
“…Thomson et al, 2012b). The act of taking an object into one's hands can be a 20 powerful experience (Samuels, 2008) particularly in the context of a hospital environment where opportunities for tactile stimulation are often minimal for long periods of time (Ander et al 2013).…”
Section: Wellbeing and Engagement Processesmentioning
confidence: 99%
“…[8][9][10][11] Quantitative measures showed significant increases in participant wellness and happiness scores. [8][9][10] Qualitative analysis revealed that patients 'used the heritage objects combined with tailored and easy social interaction, sensory stimulus and learning opportunities to tap into concerns about identity, emotions, energy levels and motivation' (pp. [8][9][10][11][12].…”
mentioning
confidence: 99%
“…[8][9][10] Qualitative analysis revealed that patients 'used the heritage objects combined with tailored and easy social interaction, sensory stimulus and learning opportunities to tap into concerns about identity, emotions, energy levels and motivation' (pp. [8][9][10][11][12]. 11 in a mixedmethods study using a pre-post design within an art gallery, outcomes showed that viewing and making art by people with dementia had an impact on episodic memory and verbal fluency.…”
mentioning
confidence: 99%
“…Studies of museum object handling, for example, show significant benefits for a range of patients in hospitals and care homes by improving mental and physical functioning, providing a positive experience during the hospital stay, and improving patient-doctor/carer communication (Ander, Thomson, Blair, et al, 2013;Chatterjee, Vreeland, & Noble, 2009;Lanceley et al, 2012;Paddon et al, 2013;Solway, Camic, Thomson, & Chatterjee, 2015;Thomson & Chatterjee, 2014a, 2014bThomson et al, 2012aThomson et al, , 2012b. Specific population groups and issues that museums have sought to address include children on the autism spectrum (Dunn, 2013;Yale Center for British Art, 2015), learning disabilities (Sullivan, 2015), cancer patients (Thomson et al, 2012a) and severe mental health problems Colbert, Cooke, Camic, & Springham, 2013). Camic and Chatterjee (2013) propose a framework whereby museums develop strategic partnerships with local healthcare authorities, health-care funders and other local museums and galleries to coordinate health and well-being programmes.…”
mentioning
confidence: 99%